The influence of body composition assessed by dual-energy x-ray absorptiometry on functional capacity of patients with chronic obstructive pulmonary disease - Gualberto Ruas; Gabriel Gomes Ribeiro; Juliane Moreira Naves; Mauricio Jamami
INTRODUCTION: The individual with chronic obstructive pulmonary disease (COPD) can experience a significant reduction of body composition, peripheral muscle dysfunction, resulting in a negative influence on functional capacity. OBJECTIVES: To analyze the influence of body composition assessed by dual-energy x-ray absorptiometry on functional capacity of patients with chronic obstructive pulmonary disease (COPD). MATERIALS AND METHODS: Eleven male patients with COPD (COPDG), seven presenting moderate obstruction and four severe, and 11 sedentary male subjects (CG) were evaluated by dual-energy x-ray absorptiometry to assess their body composition. All subjects also performed the 6-minute walk test (6MWT) and Step Test (6MST) to assess their functional capacity. RESULTS: No significant differences were found between groups for anthropometric data such as age, weight, height and body mass index (BMI). However, the COPDG presented Forced Vital Capacity (FVC), Forced Expiratory Volume in one second (FEV1), FEV1/FVC ratio, Maximal Voluntary Ventilation (MVV), Walked Distance (WD) and Number of Steps (NS) significantly lower than the CG (p < 0.05, Student's t-test). The Body Bone Mass (BBM), BBM%, Lean Mass (LM), LM%, and Right Lower Limb (RLL) and Left Lower Limb (LLL) were significantly lower in the COPDG when compared with the CG, presenting statistically significant positive correlations with 6MWT's WD and 6MST's NS (p < 0.05, Pearson's test). CONCLUSION: We conclude that body composition is an important prognostic factor for patients with COPD, which reinforces the importance of assessing body composition by dual-energy absorptiometry since it has demonstrated with satisfactory accuracy in clinical practice. Moreover, it is a useful parameter for evaluation and reassessment in pulmonary rehabilitation programs.